Current challenges in the treatment of severe Clostridium difficile infection: early treatment potential of fecal microbiota transplantation. (April 2017) - van Beurden, Yvette H.; Nieuwdorp, Max; van de Berg, Pablo J. E. J.; Mulder, Chris J. J.; Goorhuis, Abraham
Fecal microbiota transplantation (FMT) is a very effective treatment for recurrent Clostridium difficile infection (CDI). Less is known about the application of FMT as a curative treatment of severe or complicated CDI. In this review, we present and discuss evidence supporting the curative use of FMT in severe or complicated CDI. We performed a literature search in PubMed and Embase for studies on the curative use of FMT in severe or complicated CDI. In addition, we describe a patient with severe CDI not responding to initial antibiotic treatment, who was successfully treated with curative FMT. We found 23 reports (12 case reports; 11 case series) about FMT as treatment for severe or complicated CDI. The patients described all had severe or complicated CDI, did not respond to conventional CDI antibiotic treatment and received FMT as last resort treatment. Patients were treated with (sequential) FMT, whether or not followed by additional antibiotic treatment for CDI. FMT, with or without additional antibiotic CDI treatment, appears to be a promising curative treatment option in patients with severe and complicated CDI, or only complicated CDI, who do not respond sufficiently to conventional antibiotic treatment. Treatment with FMT should be considered in these patients before proceeding to emergency bowel surgery.